The Relevance of Shaping a Pious, Intelligent, and Leadership Character in Relation to the Effectiveness of Achieving a Golden Indonesia in 2045 (Universitas Pamulang, 2025)
This research is motivated by Indonesia as a country rich in natural resources and its diversity of culture, ethnicity, race, religion and language. So in this case Indonesia has great potential to become a developing and advanced nation. However, the reality is still far from this reality due to several factors including still depending on natural resources to meet all its needs, human resources that are lacking in innovation, the rise of KKN (Corruption, Collusion and Nepotism) within the structure of state officials and economic and social inequality. The purpose of this study 1) To determine the role of the state in providing optimal services to fulfill the rights of the people as protected by the constitution. 2) To determine the formulations formed by the state in relation to the roadmap towards Indonesia Emas 2045. 3) To determine the relevance of pious, intelligent and capable leadership characters in relation to the effectiveness of Indonesia Emas 2045. This study uses a qualitative method using a descriptive analysis approach by digging up information directly from the community and through a scientific literature approach, both books, journals and information related to the object of the study. The results of this study can be concluded 1) The Role of the State in Managing and Regulating Citizens has a fundamental role in providing basic services in the form of education, health, and social protection. 2) The State Roadmap Towards Golden Indonesia 2045 where Bappenas has established 7 directions of education policy 2025-2045 which include the acceleration of 13 years of compulsory education, strengthening STEAM-based higher education, improving the quality of teaching, Islamic boarding school education, vocational, educator professionalism, to education governance. 3) The Character of Pious, Intelligent, and Capable of Leading are these three characters complement each other and cannot be separated in order to achieve the generation of Golden Indonesia 2045.